The Ifugao alim literature its content and possible implication for education - Indunan, Pedro D. 1925- (s.n.], 1970)
The aim of the study is to investigate the content of the Ifugao Alim literature and its possible implications for education. This study about Alim, one of the undocumented folk literature of the country, furnishes the cue to its epic characteristics and divulges its content. The Alim content, if properly recorded, translated, and documented, can provide not only instructional materials but valuable information concerning the Rice Terrace Builders of Ifugao - their life, culture, and history.